ANALISIS KONSEP ARSITEKTUR NEO-VERNAKULAR PADA PERANCANGAN MALL PELAYANAN PUBLIK DI JEPARA - Rizqi, Muhammad (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo, 2024)
Neo-vernacular architecture is a movement that developed during postmodernism, an architectural movement that emerged in the mid-1960s. Postmodernism emerged in connection with the protest of modernist architects against monotonous models (block-shaped buildings), which were believed to have no character that could distinguish buildings from other buildings. The method used in this research is a qualitative method with descriptive analysis. In this case the application of neo-vernacular architecture in the construction of the Public Service Mall Building